Black woman, indoctrination of the male, and subversion of the patriarchy in Ngugi’s Weep Not, Child - Nasser Maleki,; Pedram Lalbakhsh, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The present paper approaches Ngugi’s Weep Not, Child from a socialist feminist point of view to foreground women’s multi-dimensional oppression in the novel and to highlight their attempts to subvert it. While the male characters of the novel have received, more or less, enough attention the female characters seem to be marginalised by the critics who have discussed the female characters more in terms of their relation to the story’s male characters. Analysing facets of oppression like sexuality, motherhood, mothering, and domestic labour, we argue that Ngugi establishes a collage of all merits and qualities that women have in terms of leadership and messianic role. In his Weep Not, Child, Ngugi shows us that women’s sound judgment and suppressed voice can be an effectively important factor in bringing liberation and equality to people’s life. The findings of this study demonstrate that, in contrast to his male characters, Ngugi’s female characters are more reliable and more dependable in establishing a political plan to achieve liberation and equal rights. This is while women are abusively exploited and ignored by the men whose impulsive decisions and miscalculated actions bring ruin to both family and society. Ironically, while the patriarchal system aims to metamorphose women’s identity, destroy their ego, and affect their confidence and independence, women are clever enough to put emphasis on education as one extremely important sub-strategy to indoctrinate and educate the next generation’s male members against patriarchy and patriarchal conduct.